Correlation between Galectin-3 and Early Herpes Zoster Neuralgia and Postherpetic Neuralgia: A Retrospective Clinical Observation - Tingting Wang; Yong Fei; Ming Yao; Jiachun Tao; Jiajia Deng; Bing Huang (Pain Research and Management)
This study aims to explore the value of serum galectin-3 in patients with herpes zoster neuralgia (HZN) and postherpetic neuralgia (PHN) and other factors influencing HZN and PHN occurrence. Samples from forty patients with herpes zoster neuralgia (HZN) (Group H), 40 patients with nonherpes zoster neuralgia (Group N), and 20 cases of health check-up were collected. Patients were divided into PHN group (Group A) and non-PHN group (Group B) according to the occurrence of PHN in Group H. Galectin-3, T-lymphocyte subsets, and IL-6 were recorded in all patients. The changes of galectin-3 in patients with early HZN and PHN were analyzed by single-factor analysis and multifactor analysis. The age (P=0.012) and NRS scores (P<0.001) of PHN patients were significantly higher than those of non-PHN patients and other neuralgia patients. The ratio of CD3+ (F = 80.336, P<0.001), CD4+ (F = 12.459, P<0.001) lymphocyte subsets, and CD4+/CD8+ (F = 15.311, P<0.001) decreased significantly in PHN patients. The level of blood IL-6 (F = 139.446, P<0.001) in PHN patients was significantly increased. Serum galectin-3 was significantly higher in HZN patients than in PHN patients (P<0.05); IL-6 (OR = 10.002, 95% CI: 3.313–30.196, P<0.001) and galectin-3 (OR = 3.719, 95% CI: 1.261–10.966, P=0.017) were the risk factors for HZN; galectin-3 (OR = 17.646, 95% CI: 2.795–111.428, P=0.002) was also the risk factor for PHN. ROC curve analysis also showed that serum galectin-3 was a better predictor of poor prognosis (AUC = 0.934, P<0.001). Therefore, as an independent risk factor of HZN and PHN, serum galectin-3 may be used as a new biochemical marker in clinical practice.